Air Quality Impact Analysis of Traffic Emissions in Metropolitan Areas - Lestari, Putri Maharani; Du, Wenjie; Domene, Elena (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
Urban traffic is a major contributor to air pollution, significantly affecting human health and environmental quality. This study aims to assess the impact of traffic emissions on air quality in metropolitan areas using a synthesis of empirical data and modeling studies. Data from major cities including Shanghai, São Paulo, Barcelona, Delhi, Milan, and Beijing were analyzed, focusing on pollutants such as NO₂, PM2.5, PM10, CO, and black carbon. Methods include emission inventory analysis, deep learning prediction models, bottom-up exposure modeling, and scenario simulations for traffic management interventions. Results indicate that vehicular emissions significantly elevate urban pollutant concentrations, with peak traffic hours and non-exhaust emissions amplifying exposure risks (Du et al., 2022; Pérez-Martínez et al., 2020; Piccoli et al., 2023). Fleet modernization and the adoption of eco-friendly vehicles can reduce NOx and CO concentrations by up to 47% and mitigate public health impacts (Holnicki et al., 2021; 양충헌 et al., 2013). Scenario analysis suggests that cycling promotion and low-emission zones can further improve urban air quality (Kuik et al., 2016; Soret et al., 2023). This study highlights the importance of integrated urban traffic management and policy measures in controlling air pollution.